The Decision to Buy Vegan Food is Influenced by Green Marketing, Social Media Marketing, Healthy Lifestyle, and Brand Image - Ayumi, Made Santhi; Darma, Gede Sri (Universitas KH. Abdul Chalim Mojokerto, 2025)
The development of the culinary business has increased rapidly in various countries, especially after the Covid-19 pandemic in March 2020 significantly changed people's lifestyles. Lifestyles are now more focused on health to prevent various diseases, with special attention to diet and healthy food consumption. Heart disease is one of the highest causes of death in Indonesia, with many making efforts to change their lifestyle to a healthier one, such as adopting a vegan diet. Veganism, which excludes the consumption of meat and other animal products, is becoming popular due to the various health benefits associated with it, such as reducing the risk of obesity and high cholesterol. Nonetheless, there is a global trend where people tend to choose preferred foods over healthy ones, such as increasing meat consumption without enough fiber from vegetables and fruits, which is potentially harmful to health. Excessive meat consumption is also associated with the risk of diseases such as diabetes and heart disease. This think about points to decide the impact of green promoting, sound way of life, social media showcasing, brand picture, and buy choice on vegetarian nourishment in Indonesia. The populace comprised of all Indonesian citizens over 17 a long time ancient who have devoured vegetarian nourishment. The test estimate comprised 190 respondents. The information investigation demonstrate utilized was Auxiliary Condition Show (SEM) with SmartPLS 4. Based on the comes about of information preparing utilizing SmartPLS 4, it can be concluded that there's a noteworthy and positive impact of brand picture on buy choice, green showcasing on brand picture, sound way of life on brand picture, solid way of life on buy choice, and social media showcasing on buy choice. Be that as it may, green showcasing on buy choice and social media showcasing on buy choice have a critical negative impact. It is known that the impact of brand picture on buy choice is the biggest in terms of impact estimate and centrality in this ponder.